Determinants of Education Outcomes Quality of College Students in Besuki Raya Region, Indonesia (Case Study During the Covid-19 Pandemic) - Retna Anggitaningsih; Moch. Chotib (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
This study tries to explain the effect of understanding the importance of online studying, readiness for the use of electronic information technology on the quality of educational outcomes through the learning spirit of private college students in Besuki Raya Region, Indonesia. The objects of observation are four large private universities in Besuki Raya Region, namely: University of 17 Agustus 1945 in Banyuwangi, University of Abdulrachman Saleh in Situbondo, Mochamand Sroedjie University in Jember, University of Muhamadiyah in Jember, and STIE Mandala in Jember. Each of the five universities selected 40 students, in various semesters, so the number of respondents = 200 students. The analytical method used is a Structural Equation Model (SEM). The findings indicate that: (1) understanding the importance of online studying has a significant positive effect on student enthusiasm for learning; (2) readiness to use electronic information technology has a significant positive effect on student learning enthusiasm; (3) understanding the importance of online studying has no significant effect on the quality of educational outcomes; (4) readiness to use electronic information technology has a significant positive effect on the quality of educational outcomes, and (5) enthusiasm for learning has a significant positive effect on the quality of student education outcomes.